IMMU-16. CHARACTERIZING TUMOR-IMMUNE INTERACTIONS IN DIFFUSE INTRINSIC PONTINE GLIOMA. Issue 2 (22nd June 2018) - Lieberman, Nicole; Kovar, Heather; DeGolier, Kole; Davis, Amira; Hoglund, Virginia; Stevens, Jeffrey; Winter, Conrad; Deutsch, Gail; Vitanza, Nicholas; Leary, Sarah; Crane, Courtney
Abstract: Diffuse Intrinsic Pontine Glioma (DIPG) is a universally fatal brain tumor diagnosed in approximately 300 children in the US each year. Radiation modestly extends patient survival and provides temporary relief from symptoms, however, surgical resection is impossible due to the tumor's location in the brainstem, and no chemotherapeutics have shown any efficacy; death generally occurs less than a year after diagnosis. Due to its ability to specifically eliminate tumor cells while leaving healthy tissue intact, immunotherapy could be a major breakthrough in the treatment of DIPG. As a first step towards the rational development of DIPG-specific cellular immunotherapy, we have characterized the immune microenvironment of DIPG tumors using IHC analysis of TMAs and Nanostring transcript analysis of frozen tumor samples. In contrast to pediatric and adult high-grade cortical gliomas (HGGs), DIPGs exhibit minimal infiltration with CD163+ myeloid cells or CD8+ T cells, consistent with their low mutational burden. Furthermore, unlike adult HGGs in particular, DIPG tumors had low levels of classical immunosuppressive factors including PD-L1, TGFβ, and IL-10. To directly examine the effects of DIPG cells on immune cells, we co-cultured primary tumor cells with immune cells from healthy donors. DIPG tumor cells did not polarize macrophages towards a pro-tumor phenotype, while U87 adult GBM cells did. Furthermore, DIPG cells did not slow T cell proliferation or prevent IFNγ production, while U87 cells did. Together, this suggests that although DIPG tumors are not inducing an immune response, adoptively transferred anti-tumor immune cells will not need to overcome an immunosuppressive microenvironment.